FLUORESCENCE STUDIES FOR IN SITU MONITORING OF THE HYDROLYSIS AND POLYMERIZATION REACTIONS OF ORGANICALLY –MODIFIED TETRAMETHYLORTHOSILICATE - Eko Sri Kunarti (Indonesian Journal of Chemistry, 2005)
Monitoring of hydrolysis and condensation polymerization reactions of tetramethylorthosilicate-organosiloxane have been carried out. Proton transfer from the excited state of 8-hydroxy-1,3,6-pyrenetrisulfonic acid trisodium salt (pyranine) to surrounding water molecules was used as a sensitive fluorescence method for following the kinetics of water consumption during the early stages of the sol-gel polymerisation process. Changes in water/silane ratio, type of organosiloxane, mol ratio of organosiloxane to silica precursor and pH affected markedly the kinetic behavior of the hydrolysis and condensation reaction of tetramethylorthosilicate.